GRBL Based 3 Axis CNC Milling Design - Azam Milah Muhamad; Radhi Maladzi; Luqyana, Dhiya; Damis, Candra; Nurjanah, Darul (Jurnal Mekanik Terapan, 2025)
This study presents the design and fabrication of a GRBL-based 3-Axis CNC Milling Machine for laboratory and small-scale industry applications. The system is controlled by an Arduino Uno using GRBL firmware, with NEMA 17 stepper motors and a DC 775 spindle. The Quality Function Deployment (QFD) method was applied to align the design with user requirements. The machine features a 600 × 400 mm working area, 200 Watt power consumption, and spindle speed ranging from 3,000 to 12,000 RPM. Testing results demonstrate high precision and energy efficiency. This machine is suitable for digital manufacturing education and prototyping.